Restoration of artworks in the Berlin royal picture collection between 1797 and 1830 - Robert Skwirblies (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2012)
The efforts on conservation and restoration of pictures in the Prussian royal collections increased in the first decades of the 19th century. Local painters were replaced first by French and Italian restorers, then by German professionals that founded an own workshop, related to the new public art museum in Berlin. Systematic, frugal restorations and control by the authorities superseded former disregard and selective measures.